Latest Development of Molded Inductor in Terms of Improvements in Material Options and Manufacturing Process - Fatchurrohman, Nanang; Ishak, Ismayuzri (Universitas Putra Indonesia YPTK Padang, 2025)
This paper presents a comprehensive review of the development of molded inductor technology, emphasizing its advantages over conventional inductors. Molded inductors have emerged as a critical component in modern electronic systems due to their superior performance in high-temperature environments, high power density, compact design, and enhanced mechanical integrity. These benefits are largely attributed to the unique construction process, in which the magnetic core is molded directly around the wire and lead frame, eliminating the need for pre-fabricated cores. Such an approach results in improved structural strength and electrical efficiency. In addition to exploring the technological superiority of molded inductors, the paper examines their current applications across various industries. These include the automotive sector, power electronics, industrial automation, and consumer devices, where the demand for miniaturized yet powerful and reliable components continues to grow. The discussion then shifts to the current manufacturing processes employed in producing molded inductors. This includes automated coil winding, precision molding using magnetic powder and resin mixtures, and post-molding treatments such as heat curing and surface finishing. the paper concludes with practical recommendations for manufacturers. These include adopting automated production lines, implementing stringent quality control and testing protocols. Such strategies are essential for staying competitive in a rapidly evolving technological landscape and meeting the rising expectations for performance, reliability, and sustainability in electronic components.